Motivation and Ability: Unpacking Underperforming Firms’ Risk Taking - Ref, Ohad; Hu, Songcui; Milyavsky, Maxim; Feldman, Naomi E.; Shapira, Zur (Organization Science, 2024)
Do firms take more or less risk in response to performance shortfalls? Although the behavioral theory of the firm (BTOF) has been a guiding framework in this area, empirical evidence remains inconclusive. Moreover, empirical work has largely failed to distinguish between firms’ motivation to take risks and their ability to do so. In this study, recognizing the distinct roles played by these two components, we specifically focus on risk-taking motivation. Drawing on March and Shapira’s shifting-focus-of-attention model, we highlight that firms’ motivation to take risks is contingent on their chosen reference points and the shifts between them. We propose that, on average, risk-taking motivation exhibits a positive monotonic relationship with performance shortfalls, a sequence involving an initial increase, subsequent leveling off, and then a renewed increase. To advance the theory of risk-taking motivation, we extend our inquiry to consider the moderating effect of concern for firm survival and subsequently explore factors influencing this concern. Furthermore, we investigate a critical implication of differentiating risk-taking motivation and ability. Because of the mismatch between motivation and ability, underperforming firms take the greatest risks when their performance is moderately below aspirations, with motivation and ability being at moderate levels, leading to an inverted U-shaped relationship between performance shortfalls and risk taking. Empirical evidence derived from experiments and archival data supports our theoretical predictions. This study contributes to the BTOF literature by demonstrating that underperforming firms’ risk-taking behavior is jointly determined by their motivation, ability, focus of attention, and concern for survival. Funding: This work was supported by the Israel Science Foundation [Grant 677/20]. Supplemental Material: The online appendices are available at https://doi.org/10.1287/orsc.2020.13953 .